# Problem: You may want to reference (Pages 186 - 190)Section 5.7 while completing this problem.Given 2 SO2(g) + O2(g) → 2 SO3(g), which of the following equations is correct?(a) ΔH˚f[SO3] = ΔH˚rxn – ΔH˚f[SO2](b) ΔH˚f[SO3] = ΔH˚rxn + ΔH˚f[SO2](c) 2ΔH˚f[SO3] = ΔH˚rxn + 2ΔH˚f[SO2](d) 2ΔH˚f[SO3] = ΔH˚rxn – 2ΔH˚f[SO2](e) 2ΔH˚f[SO3] = 2ΔH˚f[SO2] – ΔH˚rxn

###### FREE Expert Solution

Balanced Reaction: 2 SO2(g) + O2(g) → 2 SO3(g)

$\overline{){\mathbf{∆}}{{\mathbf{H}}}_{{\mathbf{rxn}}}{\mathbf{=}}{\mathbf{∆}}{{\mathbf{H}}}_{\mathbf{f}\mathbf{,}\mathbf{products}}{\mathbf{-}}{\mathbf{∆}}{{\mathbf{H}}}_{\mathbf{f}\mathbf{,}\mathbf{reactants}}}$

86% (172 ratings)
###### Problem Details

You may want to reference (Pages 186 - 190)Section 5.7 while completing this problem.

Given 2 SO2(g) + O2(g) → 2 SO3(g), which of the following equations is correct?
(a) ΔH˚f[SO3] = ΔH˚rxn – ΔH˚f[SO2]
(b) ΔH˚f[SO3] = ΔH˚rxn + ΔH˚f[SO2]
(c) 2ΔH˚f[SO3] = ΔH˚rxn + 2ΔH˚f[SO2]
(d) 2ΔH˚f[SO3] = ΔH˚rxn – 2ΔH˚f[SO2]
(e) 2ΔH˚f[SO3] = 2ΔH˚f[SO2] – ΔH˚rxn